Cell-Free Fat Extract Prevents Tail Suspension–Induced Bone Loss by Inhibiting Osteocyte Apoptosis - Xu, Mingming; Du, Jingke; Cui, Junqi; Zhang, Shuangyan; Zhang, Shuhong; Deng, Mingwu; Zhang, Wenjie; Li, Hanjun; Yu, Zhifeng (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: As the space field has developed and our population ages, people engaged in space travel and those on prolonged bed rest are at increasing risk for bone loss and fractures. Disuse osteoporosis occurs frequently in these instances, for which the currently available anti-osteoporosis agents are far from satisfactory and have undesirable side effects. CEFFE is a cell-free fraction isolated from nanofat that is enriched with a variety of growth factors, and we set out to investigate its potential therapeutic effects on disuse osteoporosis. Methods: A tail suspension-induced osteoporosis model was applied in this study. Three weeks after tail suspension, CEFFE was intraperitoneally injected, and PBS was used as a control. The trabecular and cortical bone microstructure of the tibia in each group was assessed by μCT after four weeks of administration. Osteocyte lacunar-canalicularity was observed by HE and silver staining. In vitro, MLO-Y4 cell apoptosis was induced by reactive oxygen species (ROSUP). TUNEL staining and flow cytometry were used to detect apoptosis. CCK-8 was used to detect cell proliferation, and western blotting was used to detect MAPK signaling pathway changes. Results: CEFFE increased the bone volume (BV/TV) and trabecular number (Tb.N) of trabecular, and increase the thickness of the cortical bone. HE and silver staining results showed that CEFFE reduced the number of empty lacunae and improved the lacuna-canalicular structure. CEFFE promoted osteocyte proliferative capacity in a dose-dependent manner. CEFFE protected MLO-Y4 from apoptosis by activating the serine/threonine-selective protein kinase (ERK) signaling pathways. Conclusions: CEFFE attenuated immobilization-induced bone loss by decreasing osteocyte apoptosis. CEFFE increased the survival of osteocytes and inhibited osteocyte apoptosis by activating the ERK signaling pathway in vitro.